2021
DOI: 10.1038/s41598-021-84498-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of microstructure dependence of magnetic flux trapping in niobium

Abstract: Elemental type-II superconducting niobium is the material of choice for superconducting radiofrequency cavities used in modern particle accelerators, light sources, detectors, sensors, and quantum computing architecture. An essential challenge to increasing energy efficiency in rf applications is the power dissipation due to residual magnetic field that is trapped during the cool down process due to incomplete magnetic field expulsion. New SRF cavity processing recipes that use surface doping techniques have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Without prior deformation or LAGBs, the lower number of defects that enable transport and/or concentration of subsurface hydrogen may prevent the formation of large hydrides within the bulk crystal, and favor formation in a LAGB. Recent results also confirm that the LAGB and very fine grains with limited grain growth lead to early flux penetration [55,56]. Nevertheless, the fact that bulk flux penetration occurs at lower fields following annealing suggests that residual dislocations surrounding scars and LAGBs within scars may facilitate bulk flux penetration more easily than when hydrides are present, suggesting that hydride scar dislocation substructure may facilitate trapped flux more effectively than hydrides.…”
Section: Bulk Flux Penetration and Trapping Caused By Hydrides Nuclea...mentioning
confidence: 78%
See 1 more Smart Citation
“…Without prior deformation or LAGBs, the lower number of defects that enable transport and/or concentration of subsurface hydrogen may prevent the formation of large hydrides within the bulk crystal, and favor formation in a LAGB. Recent results also confirm that the LAGB and very fine grains with limited grain growth lead to early flux penetration [55,56]. Nevertheless, the fact that bulk flux penetration occurs at lower fields following annealing suggests that residual dislocations surrounding scars and LAGBs within scars may facilitate bulk flux penetration more easily than when hydrides are present, suggesting that hydride scar dislocation substructure may facilitate trapped flux more effectively than hydrides.…”
Section: Bulk Flux Penetration and Trapping Caused By Hydrides Nuclea...mentioning
confidence: 78%
“…However, recent systematic studies do indicate that a grain size or GB density relationship with flux penetration behavior exists. These studies show that flux penetration and expulsion is easier in large grains resulting from grain growth to a size greater than 100 µm that may sweep out LAGBs, whereas penetrating flux gets trapped when the grain sizes are of a finer dimension of ∼30-50 µm [55], in which the likelihood of GB facets being aligned with the magnetic field would be larger.…”
Section: Dislocation Network In Turn Are Preferred Sites Formentioning
confidence: 92%
“…In addition, the metallurgical state with larger grain size is expected as the annealing temperature is increased [21]. The fine-grain recrystallized microstructure with an average grain size of 10-50 µm leads to flux trapping even with a lack of dislocation structures in grain interiors and larger grain sizes beyond 100-400 µm do not lead to preferential flux trapping, as observed directly by magneto-optical imaging [22]. In order to obtain repeatable and consistent cavity performance and improve process control, it is important to understand the relationship between microstructure, flux trappig and eventual cavity performance.…”
Section: Introductionmentioning
confidence: 82%
“…Even though, the final surface preparation may play some role on the initial condition of rf surface and successive baking duration, the cavity TE1-05 showed higher flux trapping sensitivity compared to cavity TE1-06. Furthermore, the cavity TE1-06 was fabricated from cold worked Nb, may have less density of dislocations and better recrystallization compared to TE1-05 cavity, leading to lower flux trapping sensitivity [14,19]. The 𝑄 0 vs. 𝐸 𝑎𝑐𝑐 measurements at 2.0 K showed that the high-field Q-slope is eliminated just after 3 hours of baking at 120 • C.…”
Section: Discussionmentioning
confidence: 99%